2009
DOI: 10.1590/s1519-69842009000100010
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of the parasitic endohelminth community of Piaractus mesopotamicus (Holmberg, 1887) (Characiformes) from Aquidauana and Miranda Rivers, Pantanal, state of Mato Grosso do Sul, Brazil

Abstract: In this study the structure and diversity of the endohelminth community, as well as its interactions with 73 specimens of Piaractus mesopotamicus are described. The fish were caught in Aquidauana and Miranda rivers, both located in the Pantantal region, in the state of Mato Grosso do Sul. A total of 608,788 specimens of helminthes were found, representing five species: Dadaytrema oxycephala, Chabaudinema americanum, Spectatus spectatus, Rondonia rondoni and Echinorhynchus jucundum. D. oxycephala was more preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
2
7
0
1
Order By: Relevance
“…Infection by R. rondoni in pacu has been reported (Costa, 1963;Martins and Urbinati, 1993;Campos et al, 2009). The occurrence of diseases associated with R. rondoni infestation is not common (Tatcher, 1991) even with record high infection intensities (675-49476), however nematodes can cause obstruction of the intestinal lumen at a high intensity of infection (Campos et al, 2009). There are several reports of mortality of pacu affected by these parasites (nematodes and monogeneans) in the Brazilian fish farms.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Infection by R. rondoni in pacu has been reported (Costa, 1963;Martins and Urbinati, 1993;Campos et al, 2009). The occurrence of diseases associated with R. rondoni infestation is not common (Tatcher, 1991) even with record high infection intensities (675-49476), however nematodes can cause obstruction of the intestinal lumen at a high intensity of infection (Campos et al, 2009). There are several reports of mortality of pacu affected by these parasites (nematodes and monogeneans) in the Brazilian fish farms.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, we observed the prevalence (100%) and intensity of infection (230-420) by nematodes in control fish and various infective stages (larvae, juveniles, adults, ovigerous females and with larvae) but again with no mortality. The high prevalence and intensity of infection by R. rondoni in pacu can be explained by endogenic multiplication of the parasite in fish and the specificity of this nematode by the host as postulated by Campos et al (2009).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Its type species, Spectatus spectatus, has been reported mainly from serrasalmid fishes (Serrasalmidae) and, less frequently, parasitizing fishes of the families Bryconidae, Doradidae and Pimelodidae, in the Paraná River basin in Brazil and Argentina (Travassos, 1923;Travassos and Kohn, 1965;Hamann, 1982aHamann, , 1982bMasi Palláres, 1990;Parra et al, 1997;Moravec, 1998;Santos et al, 2003;Campos et al, 2009). Despite its widespread occurrence, the morphology of S. spectatus is not sufficiently known which has generated problems to separate Spectatus from 2 other kathlaniid genera, Falcaustra Lane, 1915 andChabaudinema Díaz-Ungría, 1968 (see Baker, 1980).…”
mentioning
confidence: 99%